2015
DOI: 10.4137/bcbcr.s29268
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus in the Treatment of Metastatic Breast Cancer

Abstract: The discovery of the mammalian target of rapamycin (mTOR) molecular pathway has brought insight into its vital role in breast cancer pathogenesis. Several clinical trials have shown that the mTOR inhibitor everolimus could improve patient outcomes in several subtypes of breast cancer, including hormone receptor–positive, human epidermal growth factor receptor–negative metastatic disease that has progressed after prior endocrine therapy. This review summarizes findings from clinical trials that have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 32 publications
(74 reference statements)
1
39
0
1
Order By: Relevance
“…Panobinostat in combination with bortezomib and dexamethasone has been approved for use in treatment-refractory myeloma patients(8). Additionally, everolimus (9) and everolimus plus exemestane (10) has been approved for treatment in breast cancer. Entinostat (MS-275, an HDACi) was given breakthrough status in combination with exemesthane after a phase II trial demonstrated improvements in progression free survival and overall survival (11) and is currently being evaluated in a phase III trial in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Panobinostat in combination with bortezomib and dexamethasone has been approved for use in treatment-refractory myeloma patients(8). Additionally, everolimus (9) and everolimus plus exemestane (10) has been approved for treatment in breast cancer. Entinostat (MS-275, an HDACi) was given breakthrough status in combination with exemesthane after a phase II trial demonstrated improvements in progression free survival and overall survival (11) and is currently being evaluated in a phase III trial in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus was originally approved for renal cancer in 2009, as immunosuppressant during renal transplants in 2010 and for pancreatic cancer in 2011. A phase III clinical trial 'Breast Cancer Trial of Oral Everolimus-2 (BOLERO-2)' that included everolimus in combination with exemestane was successfully completed in 2012 leading to the approval of everolimus by US FDA for the treatment of HR + , HER2 − advanced metastatic cancers that are resistant to letrozole or anastrazole [125,126].…”
Section: Mtor Kinase Inhibitormentioning
confidence: 99%
“…(1) mTOR Inhibitors Rapamycin and its analogues (rapalogs, e.g., sirolimus, temsirolimus, everolimus), which inhibit mTORC1 activity, are considered the first clinical PI3K signaling inhibitors [88]. Although temsirolimus is FDA approved for treating advanced renal cell carcinoma and everolimus is approved for the treatment of advanced breast cancer, nonfunctional gastrointestinal and lung neuroendocrine tumors, and renal cell carcinoma, rapalogs are not yet approved for the treatment of EC and are under development [89][90][91].…”
Section: Pi3k/akt/mtor Signaling Pathway Inhibitorsmentioning
confidence: 99%